Is calorie restriction with sodium-glucose cotransporter 2 inhibitor dapagliflozin a better option for type 2 diabetes mellitus management? - Ruby Dhar; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences, 2025)
In a recent multicentric, double-blinded, randomized, placebo-controlled trial by Liu et al., involving 328 subjects aged 20–70 years with type 2 diabetes for ~ 6 years and with body mass index >25, dapagliflozin (10 mg/day or placebo) with calorie restriction resulted in a significantly higher rate of remission of diabetes compared with calorie restriction alone. The main objectives evaluated are diabetes remission (characterized as glycated hemoglobin